Analisis Rasio Keuangan pada Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia - Nasha Petronella Queen; Rahman Amrullah Suwaidi (Journal of Management and Bussines (JOMB), 2023)
The purpose of this study was to determine the effect of liquidity, leverage and activity on profit growth with company size as a moderating variable in state-owned companies listed on the Indonesia Stock Exchange for the 2018-2021 period. This research method is descriptive quantitative. The sampling technique is purposive sampling. The data analysis method used in this study is multiple linear regression analysis and moderated regression analysis. The results showed, a) the ratio of liquidity to profit growth has a coefficient value of 0.002 and a sig. 0.039 < Î± = 0.05 with significant (positive) results; b) the ratio of leverage to profit growth has a coefficient value of -0.097 and a sig. 0.832 > Î± = 0.05 with non-significant (negative) results; c) the ratio of activity to profit growth has a coefficient value of 5.151 and a sig. 0.002 < Î± = 0.05 with significant results (positive); d) company size moderates the relationship between the liquidity ratio and profit growth cannot be analyzed because the results of data processing show excluded variables in the moderating variable x1*z; e) company size moderates the relationship between the leverage ratio on profit growth has a coefficient value of 0.003 and a sig. 0.483 > Î± = 0.05 with non-significant (positive) results; f) company size moderates the relationship between activity ratio to profit growth has a coefficient value of -0.153 and a sig. 0.003 < Î± = 0.05 with significant (negative) results. In conclusion, liquidity and activity contribute to profit growth and company size can moderate the relationship between activity and profit growth. Meanwhile, leverage does not contribute to profit growth and company size does not moderate the relationship between leverage and profit growth. Keywords: Activity, Leverage, Liquidity, Profit Growth, Company Size